Synthesis, crystal structure, microstructure and electrical behaviour of systems Sr1-xLaxSnO3 and SrSn1-xNixO3 (x≤0.10) - Kumar Mahapatra M.; Singh P.; Kumar D.; Parkash O. (My University, 2025)
Undoped and donor doped SrSnO3 is used as a humidity sensor. The sensitivity increases with increasing donor substitution. Similarly acceptor doped SrSnO3 has high value of electrical conductivity. In the present investigation, compositions with x≤0.10 were synthesised in the systems Sr1-xLaxSnO3 and SrSn1-xNixO3 by solid state ceramic route to explore the possible applications as a capacitor or sensor materials. All the compositions were found to form solid solutions and have orthorhombic crystal structure. Average grain size is in the range 0.7-1.2 μm. Densities of all the samples are >90% of the theoretical density. The electrical conduction behaviour of these systems was investigated by the measurement of Seebeck coefficient α and DC conductivity in the temperature range 300-1100 K. These materials exhibit p type semiconduction. Conduction occurs by diffusion of doubly positively charged oxygen vacancies. Electrical resistivity of all these three compositions is very high up to 300°C. These materials may be used as capacitor materials over a considerable range of temperature above room temperature. © 2006 Institute of Materials, Minerals and Mining.